Video data analysis of online live shopping streamers on Shopee - Pathia, Laelatul; Cempaka, Putri Surya; Yakob, Freddy (Privietlab, 2025)
This research aims to identify and formulate aspects that influence buyer decisions and the behavioral impulses that emerge from consumers when streamers conduct live shopping on the Shopee marketplace. This study aims to determine the close relationship between streamers and their viewers, thus influencing increased sales. In Indonesia, sales activities through marketplaces have experienced a significant increase, with a variety of available applications and features. Therefore, a method is needed that is not only informative, but also visually appealing, emotionally, communicative, and has an impact on improving the community's economy. This study aims to develop verbal and nonverbal methods for streamers during live shopping. This is an effective solution for identifying patterns that influence buyer decisions. This research method uses Video Data Analysis (VDA) and visual studies, namely methods that focus on what is depicted in visual data. Visual data are used to depict, describe, or analyze social phenomena through Visual Studies, Multimodal Interaction Analysis, Ethnography, and Experimental Behavioral Studies. Researchers will focus on the situational dynamics and behaviors of video and visual streamers during live shopping for various products, including fashion, food, household items, and electronics. The expected outcome of this research is a concept of verbal and nonverbal communication in live shopping that is relevant to all types of marketplaces.